MENINGKATKAN PARTISIPASI AKTIF SISWA DALAM PEMBELAJARAN FIQIH MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI SMP NEGERI 1 SURO - Hadi Musra Hadi Musra (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2025)
This study aims to increase students' active participation in learning Fiqh through Contextual Teaching and Learning (CTL) approach at SMP Negeri 1 Suro. The method used in this research is classroom action research (PTK) with two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were VIII grade students who experienced low participation in Fiqh learning. Data collection techniques used observation, interviews, questionnaires, and documentation.The results showed that the application of the CTL approach was able to significantly increase students' active participation. In the first cycle, student participation increased from 40% to 65%, while in the second cycle it increased to 85%. This increase occurred because the CTL method makes learning more contextual, meaningful, and relevant to students' daily lives. In addition, this approach also encourages students to be more active in discussing, working in groups, and connecting the material with their experiences. Thus, the Contextual Teaching and Learning (CTL) approach is proven effective in increasing students' active participation in learning Fiqh. Teachers are advised to continue developing contextual and innovative learning strategies so that students are more interested and motivated in learning.